Street Vendors: Orientation and Mindset of Entrepreneurship on Entrepreneurial Intention - Muhammad Sirojuddin Amin; Heri Pratikto; Ludi Wishnu Wardana (Cita Konsultindo Research Center, 2024)
The number of street vendors in Indonesia is an exciting thing to research. This relates to their decision to become an entrepreneur. Several interesting points are identified as supporting their entrepreneurial intentions, including entrepreneurial orientation, entrepreneurial mindset, and innovative work behaviour, which strengthen relationships. The problem often faced by street vendors is a need for more innovation so they do not have a competitive edge. On the other hand, intense competition usually becomes an obstacle in running a business. Therefore, innovation and ideas are needed to make them survive and even win the contest. The population in this study consists of street vendors spread across Greater Malang, with a sample size of 200 respondents. The method used in this research is PLS-SEM analysis. Entrepreneurial orientation and entrepreneurial mindset influence innovative work behaviour. A strong entrepreneurial spirit will encourage innovation. Another interesting finding is that creative work behaviour does not mediate the relationship between entrepreneurial orientation and entrepreneurial mindset on entrepreneurial intentions. There needs to be support other than entrepreneurial orientation and an entrepreneurial mindset to generate entrepreneurial intentions, such as entrepreneurship education, as well as government support related to the environment, capital, and training.